A novel wireless electromagnetic wave transmission method applicable to water injection wells and analysis of the influence factors - Zhiqiang Li; Junyan Lin; Shaojie Xing; Xiufeng Ji; Mingjiang Dang; Jianye Wang (Scientific Reports)
Abstract This research proposes a wireless extremely low-frequency electromagnetic wave communication technology applicable to the water injection well environment, which can replace the traditional wired transmission method to ensure the stable transmission of water injection well data. Given the significant obstruction of the metal casing in the water injection well to the propagation of electromagnetic waves, this study constructs a refined finite element model for wireless extremely low-frequency electromagnetic transmission in water injection wells based on the electromagnetic field theory and conducts a comprehensive and in-depth analysis of the complex communication channel. The research shows that the load impedance is a key factor affecting the transmission performance of extremely low-frequency electromagnetic waves in cased wells. In addition, this study introduces the concept of contact resistance for the first time and deeply explores its impact on the electromagnetic transmission efficiency. Based on the above theoretical findings, we propose an innovative solution, that is, wrapping insulating materials on the outside of the oil pipe to improve the transmission effect of electromagnetic waves. Verified by simulation and field experiments, this method significantly enhances the signal reception strength of the ground antenna.